Heating versus Cooling in Galaxies and Clusters of Galaxies: Proceedings of the MPA/ESO/MPE/USM Joint Astronomy Conference held in Garching, Germany, 6 - 11 August 2006 - Böhringer, Hans (Eso Astrophysics Symposia, European Southern Observatory, 2007)
This volume documents recent developments that have advanced our understanding of the heating and cooling mechanisms in galaxies and galaxy clusters. Chapters detail results from multi-wavelength observations and advances in numerical hydrodynamical simulations. An additional section covers new research findings on feedback and self-regulatory mechanisms during cosmic structure formation in general and in galaxy formation in particular.